MENINGKATKAN KINERJA KARYAWAN : ANALISIS LATAR BELAKANG PENDIDIKAN DAN GENDER PIMPINAN DENGAN INTELEKTUAL CAPITAL SEBAGAI MEDIATOR - Maulina, Risa Cahyani; Sutianingsih, Sutianingsih (ITB AAS Indonesia Surakarta, 2024)
The objective of this study is to analyze the effects of various factors, such as leadership and educational background, on employee performance. Through a quantitative research design, the study will be able to provide a definitive answer. The data collected for the study came from questionnaires sent out to 104 employees of BKK Grobogan regency. The subjects for the study were selected through the Slovin formula, and the results indicated that certain factors, such as intellectual capital, leadership, and educational background, had a positive impact on employee performance. The educational background of the subjects was also positively related to intellectual capital. In addition, leadership gender was associated with a positive impact on the performance of the employees. Keywords : leadership, educational background, employee performance